Socio-cultural Dimensions of Malnutrition among Indigenous Peoples: A study among Irulas Community of Attappady, Kerala - Abdul Kareem C. (Journal of Social Work Education and Practice, 2019)
Malnutrition is one of the major concern and one of the most important reasons of morbidity and mortality at Attappadi in Palakkad district of Kerala. Despite in Attappady various projects and other developmental programmes were implemented by government departments and various NGOs, the particular problem still arising and also reporting the child death due to malnutrition. This is a cause of great concern. The aim of this study was to determine key socioeconomic and socio-cultural dimensions and practices affecting malnutrition among Irulas community of Attappadi. As it is a fact-finding investigation, descriptive research design is employed in the study. Because Adivasi people as we know they are very sensitive and they are not well communicated their problems as common people so the researcher decided to take data separately with interview schedule for getting socio economic profile and other health related aspects the community and in-depth interview for getting socio cultural dimensions of malnutrition and life of Adivasis in Attappady. The primary data were collected from the Irula community of Attappady, the tribal block of Palakkad district in Kerala. From data interpretation and the analysis of the research malnutrition in Attappady has several socio cultural dimensions such as lack of food and nutritional security, collapse of traditional system of Adivasi people, tremendous change the agricultural system, lack of education, lack of employability, lack of good transportation and sanitation.